Peran Audit Internal : Strategi deteksi kecurangan oleh Inspektorat Kabupaten Bangkalan - Djasuli, Mohamad; Rohmi, Nurul (Account: Jurnal Akuntansi, Keuangan dan Perbankan, 2025)
The large number of fraud cases that occur in Bangkalan regency results in the increasingly important role of internal auditors in helping prevent and detect fraud. Many cases occur, namely falsifying financial reports that are made as good as possible, but the realisation is a lot of fraud. The method used in this research is descriptive qualitative with the aim of being able to describe in depth like the original. The data sources used are primary data sources because through interviews which are then analysed so that they become understandable writing. The role of internal audit is definitely needed by local government organisations in minimising fraud. Prevention and detection of fraud is not underestimated because it can have an effect on the continuity of a company in the future. The role of internal audit can be divided into 3, namely as a supervisor who can also conduct examinations, then become a consultant who can provide advice and recommendations, and finally as a catalyst that helps the management of a company. If the role of internal audit is appropriate, then fraud in an organisation can be detected early and can be resolved more quickly. The result of this study is that the role of internal audit in helping to detect fraud is very good and optimal with various strategies that have been carried out in the hope of reducing the number of frauds in the city.  Keywords: Internal Audit Role; Detection and prevention strategies; Fraud.